ANALISA SIMULASI PADA KEKUATAN MATERIAL MINI BOILER MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS (FEA) - Setiawan, Eko; Zamheri, Ahmad; Mardiana, Mardiana (Politeknik Negeri Sriwijaya, Indonesia, 2025)
The advancement of technology today supports the development of production tools in the tofu industry. One such technology in the field of energy conversion has sparked many creative ideas for its application in the industrial world. One of the energy conversion machines is the mini boiler or steam boiler. The mini boiler is capable of converting water into steam, which can be utilized for its pressure and heat. Some tofu industries have already adopted steam-generating production equipment. These conventional steam machines are made of drums that function as steam collectors. In the tofu production process, the mini boiler plays a very vital role. The mini boiler produces high-pressure steam. Therefore, it is necessary to simulate and conduct a structural analysis to improve the efficiency of the mini boiler using the Finite Element Analysis (FEA) method. The material used in this study is stainless steel. This study aims to perform a simulation analysis on the mini boiler in an effort to improve design efficiency, using a method that models and analyzes phenomena related to the system through a numerical approach. The research methodology employed is Finite Element Analysis (FEA) with the assistance of ANSYS 2023 R1 software